APPLICATION OF GRAPH COLORING IN LEARNING SCHEDULE ARRANGEMENT AT MAN 1 PROBOLINGGO - Faiqoh, Nurul; Farisi, Olief Ilmandira Ratu (NJCA (Nusantara Journal of Computers and Its Applications), 2024)
Learning schedule at MAN 1 Probolinggo has been carried out by utilizing a number processing application. However, the preparation is still done manually. This is due to the large number of teachers, study groups, subjects, and time allocation. Thus, there are still overlapping schedules. In this study, we propose graph coloring to arrange schedules at MAN 1 Probolinggo. Each vertex on the graph represents a subject in a class of X grade. Vertices which represent the subjects are connected by an edge if it taught by the same teacher or taken by the same class. Based on the data, there are 290 vertices in the graph. We used Welsh Powell Algorithm for coloring the graph and implemented by using Python. The results of this research showed that 30 different colors are needed to color the graph. This implies that the minimum period for scheduling all the subjects in each class in one week is 30 periods with one period equal to 2 lesson hours. From the graph coloring results, we obtained a class X schedule without overlap and easily rearranged according to the color groups.